2019
DOI: 10.1001/jamanetworkopen.2019.3365
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Identify Patient Risks of Prescription Opioid Addiction When Initiating Opioids for Pain

Abstract: Key Points Question How can physicians identify patients with pain for whom prescription opioids can be safely prescribed? Findings This systematic review found that a history of opioid use disorder or other substance use disorder, a mental health diagnosis, and concomitant prescription of certain psychiatric medications may be associated with an increased risk of prescription opioid addiction. However, only the absence of a mood disorder appeared useful fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 36 publications
4
103
0
5
Order By: Relevance
“…Characteristics associated with engagement in indicators of potential extra‐medical opioid use included being younger, male and having a lifetime history of pharmaceutical opioid or illicit SUDs. This is consistent with two recent systematic reviews on the risk factors for prescription opioid misuse and addiction among people with CNCP. Additionally, the identification of these risk factors for indicators of potential extra‐medical opioid use supports clinical guidelines , which suggest careful monitoring of people with substance use histories in management of CNCP with opioids.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Characteristics associated with engagement in indicators of potential extra‐medical opioid use included being younger, male and having a lifetime history of pharmaceutical opioid or illicit SUDs. This is consistent with two recent systematic reviews on the risk factors for prescription opioid misuse and addiction among people with CNCP. Additionally, the identification of these risk factors for indicators of potential extra‐medical opioid use supports clinical guidelines , which suggest careful monitoring of people with substance use histories in management of CNCP with opioids.…”
Section: Discussionsupporting
confidence: 92%
“…Monitoring of indicators of potential extra‐medical opioid use is important because they may indicate problems with pain management and are potentially associated with adverse clinical outcomes . Two recent systematic reviews examined the characteristics associated with ‘opioid misuse’ and opioid addiction . Both reviews identified similar significant associations, such as a history of substance use .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence also suggests that multiple factors help predict risk of harm when prescribing opioids for pain, including social and economic factors, medical history, and opioid formulation 910. A history of substance use disorder, personality disorder, or other mental health conditions and concomitant prescription of psychiatric drugs are indicators of higher risk of addiction to prescription opioids 9. Furthermore, overdose events are six times more likely among patients prescribed a long acting opioid than those given a short acting opioid 10.…”
Section: Reducing Harmmentioning
confidence: 99%
“…30 According to a recent review, most opioid screening tools were either based on low-quality studies or demonstrated poor performance in discriminating high-risk from low-risk patients. 31 It is our experience that patient and physician expectations also play a critical role in outcomes. Whereas systematic reviews have found that opioid therapy is perhaps the most efficacious treatment for chronic pain of various etiologies with numbers needed to treat in the 2.5 to 4 range and an average pain reduction of around 30%, it rarely completely eradicates pain.…”
mentioning
confidence: 99%